Law of health education on first aid - Witold Pawłowski; Krzysztof Goniewicz; Mariusz Goniewicz; Patrycja Misztal-Okońska; Dorota Lasota (Kazimierz Wielki University, 2018)
Polish law requires all citizens to take action in order to assist in any case, where exist the danger of loss of life and serious bodily injury of victim, even if they can prove to be ineffective. Everyone can become a participant and / or witnessed of the events where human life is endangered. Therefore everyone should have the theoretical knowledge and practical skills in first aid, and know the consequences of inaction in the event of danger to life or health of another human being. The research presents an analysis of legal acts regulating the provision of first aid in Poland. An attempt was made to organize the interpretation presented ideas to the presented material was help and guidance for trainers in first aid. Particular emphasis is placed on the realization, that not helping the man appearing in the position of threatening an imminent danger of death or grievous bodily injury commits a crime by omission. However, first aid in their duties diligently, in accordance with the current guidelines will not conflict with the law.